Subcutaneous negative pressure versus simple closure of skin incision following an emergency laparotomy: a randomized control study - Kagita, Rakesh; Mulla, Sameer Ahmed; Srinivas Pai, B.; Desai, Mallikarjun (International Surgery Journal, 2019)
Background: Surgical site infection (SSI) is a major problem associated with open abdominal surgery and is related to increased morbidity, mortality and healthcare costs. A subcutaneous negative pressure drain reduces dead space in subcutaneous tissue by preventing accumulation of fluid. The aim of present study was to establish the efficacy of a subcutaneous negative pressure for preventing SSI following exploratory laparotomy. Methods: A total of eligible 76 patients who underwent emergency abdominal surgical procedure, between October 2016 to March 2018, were randomized into subcutaneous drainage (DG) and no drainage group (NDG). Antibiotic prophylaxis was applied to each patient. The diagnosis of superficial SSI was made and was graded according to Southampton Grading System. Results: 5 patients in drain group (40) and 25 patients in no drain group (36) had incisional SSI with statistical difference (p<0.05). No statistical difference between groups was observed for age, sex, hospital stay (p>0.05). Conclusions: Subcutaneous negative pressure prevents post-operative surgical site infection significantly. Subcutaneous negative pressure drainage reduces hospital stay in a patient undergone emergency laparotomy, compared to patients in whom negative pressure drain was not placed.